2014
DOI: 10.5539/ijef.v6n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy Prediction Model: The Case of the United States

Abstract: United States has faced a growing number of corporate bankruptcies since the subprimes crisis. This paper aims to develop an econometric forecasting model constructed from three simple and easily available financial ratios. We used a matched-pair sample of US quoted firms with half of the sample filing for chapter 11 (reorganization procedure) of the United States Bankruptcy Code for the period 2000-2012 and conducted logit regression analysis. We found that this model using three simple, few correlated and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…Lee and Choi () posited that nonparametric models such as artificial neural networks could interpret nonlinear relationships among variables, but they cannot explain causal relationships between variables. Parametric models are more widely used than nonparametric models (Bredart, ). The accuracy of parametric models such as multiple discriminant analysis is higher (Bellovary, Giacomino, & Akers, ).…”
Section: Literaturementioning
confidence: 99%
“…Lee and Choi () posited that nonparametric models such as artificial neural networks could interpret nonlinear relationships among variables, but they cannot explain causal relationships between variables. Parametric models are more widely used than nonparametric models (Bredart, ). The accuracy of parametric models such as multiple discriminant analysis is higher (Bellovary, Giacomino, & Akers, ).…”
Section: Literaturementioning
confidence: 99%
“…Jan and Marimuthu (2015) used Altman"s Z score model and claimed that bankruptcy caused in different Islamic countries was just because of different performance indicators except productivity. A study was conducted by Bernanke (1981) and found that a drop in national income of banks suffered form a deterioration in portfolio quality which led to insolvency over a period of time. Chakravarthy (1986) concluded usually Altman"s Z score was not only a measure of predicting bankruptcy but also a multidimensional measure of strategic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have found that the predictive power is substantially enhanced when these measures are combined. Brédart (2014) developed an econometric forecasting model, and he found that this model using three simple and a few correlated and easily available financial ratios as explanatory variables shows a prediction accuracy of more than 80%. Dakovic et al (2010) developed statistical models for bankruptcy prediction of Norwegian firms in the limited liability sector, using the annual balance sheet information.…”
Section: Literature Reviewmentioning
confidence: 99%